Anger Self-Management Training for Chronic Moderate to Severe Traumatic Brain Injury: Results of a Randomized Controlled Trial. Issue 5 (September 2017) - Hart, Tessa; Brockway, Jo Ann; Maiuro, Roland D.; Vaccaro, Monica; Fann, Jesse R.; Mellick, David; Harrison-Felix, Cindy; Barber, Jason; Temkin, Nancy
Abstract : Objective: To test efficacy of 8-session, 1:1 treatment, anger self-management training (ASMT), for chronic moderate to severe traumatic brain injury (TBI). Setting: Three US outpatient treatment facilities. Participants: Ninety people with TBI and elevated self-reported anger; 76 significant others (SOs) provided collateral data. Design: Multicenter randomized controlled trial with 2:1 randomization to ASMT or structurally equivalent comparison treatment, personal readjustment and education (PRE). Primary outcome assessment 1 week posttreatment; 8-week follow-up. Primary Outcome: Response to treatment defined as 1 or more standard deviation change in self-reported anger. Secondary Outcomes: SO-rated anger, emotional and behavioral status, satisfaction with life, timing of treatment response, participant and SO-rated global change, and treatment satisfaction. Main Measures: State-Trait Anger Expression Inventory-Revised Trait Anger (TA) and Anger Expression-Out (AX-O) subscales; Brief Anger-Aggression Questionnaire (BAAQ); Likert-type ratings of treatment satisfaction, global changes in anger and well-being. Results: After treatment, ASMT response rate (68%) exceeded that of PRE (47%) on TA but not AX-O or BAAQ; this finding persisted at 8-week follow-up. No significant between-group differences in SO-reported response rates, emotional/behavioral status, or life satisfaction. ASMT participants were more satisfied with treatment and rated global change in anger as significantly better; SO ratings of global change in both anger and well-being were superior for ASMT. Conclusion: ASMT was efficacious and persistent for some aspects of problematic anger. More research is needed to determine optimal dose and essential ingredients of behavioral treatment for anger after TBI. Abstract : Supplemental Digital Content is Available in the Text.